2013
DOI: 10.1371/journal.pone.0060834
|View full text |Cite
|
Sign up to set email alerts
|

Artemether Combined with shRNA Interference of Vascular Cell Adhesion Molecule-1 Significantly Inhibited the Malignant Biological Behavior of Human Glioma Cells

Abstract: Artemether is the derivative extracted from Chinese traditional herb and originally used for malaria. Artemether also has potential therapeutic effects against tumors. Vascular cell adhesion molecule-1 (VCAM-1) is an important cell surface adhesion molecule associated with malignancy of gliomas. In this work, we investigated the role and mechanism of artemether combined with shRNA interference of VCAM-1 (shRNA-VCAM-1) on the migration, invasion and apoptosis of glioma cells. U87 human glioma cells were treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
33
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 52 publications
0
33
0
Order By: Relevance
“…Therefore, it is reasonable to conclude that glioma may promote the migration of BMSCs by increasing the expression of integrin α4. Additionally, we suggest that VCAM-1 and integrin α4 might interact with their own ligands in the extracellular matrix, respectively, which promote the migration in a 2-fold effect, which is similar to tumor cells such as U87MG (27,28).…”
Section: Discussionmentioning
confidence: 79%
“…Therefore, it is reasonable to conclude that glioma may promote the migration of BMSCs by increasing the expression of integrin α4. Additionally, we suggest that VCAM-1 and integrin α4 might interact with their own ligands in the extracellular matrix, respectively, which promote the migration in a 2-fold effect, which is similar to tumor cells such as U87MG (27,28).…”
Section: Discussionmentioning
confidence: 79%
“…Moreover, studies have shown that anti-VCAM-1 antibody could significantly inhibit the growth of glioma and prolong the survival of tumor bearing rats (Zhan et al, 2011). Our previous work also revealed that the interference silence of VCAM-1 not only inhibited the proliferation, invasion of glioma cell but also induced apoptosis (Wang et al, 2013a). Thus anti-VCAM-1 treatment may present a potential strategy for the therapy of glioblastoma.…”
mentioning
confidence: 77%
“…Thus anti-VCAM-1 treatment may present a potential strategy for the therapy of glioblastoma. Extracellular matrix (ECM) is considered to be a barrier against glioma metastasis (Wang et al, 2013a). The family of matrix metalloproteinases (MMPs), identified as the invasion related proteins, plays a key role in degrading ECM, which contributes to the metastasis and invasion of malignant tumors (Wang et al, 2013a).…”
mentioning
confidence: 99%
See 2 more Smart Citations